Sensitivity of Meloidogyne incognita and Rotylenchulus reniformis to Fluopyram - Faske, T. R. (J Nematol, 2015)
Fluopyram is a succinate dehydrogenase inhibitor (SDHI) fungicide that is being evaluated as a seed treatment and in-furrow spray at planting on row crops for management of fungal diseases and its effect on plant-parasitic nematodes. Currently, there are no data on nematode toxicity, nematode recovery, or effects on nematode infection for Meloidogyne incognita or Rotylenchulus reniformis after exposure to low concentrations of fluopyram. Nematode toxicity and recovery experiments were conducted in aqueous solutions of fluopyram, while root infection assays were conducted on tomato. Nematode paralysis was observed after 2 hr of exposure at 1.0 µg/ml fluopyram for both nematode species. Using an assay of nematode motility, 2-hr EC(50) values of 5.18 and 12.99 µg/ml fluopyram were calculated for M. incognita and R. reniformis, respectively. Nematode recovery in motility was greater than 50% for M. incognita and R. reniformis 24 hr after nematodes were rinsed and removed from a 1-hr treatment of 5.18 and 12.99 µg/ml fluopyram, respectively. Nematode infection of tomato roots was reduced and inversely proportional to 1-hr treatments with water solutions of fluopyram at low concentrations, which ranged from 1.3 to 5.2 µg/ml for M. incognita and 3.3 to 13.0 µg/ml for R. reniformis. Though fluopyram is nematistatic, low concentrations of the fungicide were effective at reducing the ability of both nematode species to infect tomato roots.